The Influence of International Law and International Tribunals on Harmonized or Hybrid Systems of Criminal Procedure (Washington University Global Studies Law Review, 2005)
Through two long and bloody wars and conflicts ongoing still today, humanity at the same time achieved some incremental progress during the twentieth century toward the establishment of international institutions. The Permanent Court of International Justice, its successor the International Court of Justice, and the many other tribunals and dispute settlement bodies that currently exist, were all developed in the last century. The subject of this panel is the establishment of international criminal jurisdictions able to investigate and prosecute individuals accused of international and national crimes, as well as the harmonization and incorporation of international norms and their influence upon each other.
Keywords: Criminal procedure; Harmonization of laws; International courts; International law; European Union; International; United States